2001
DOI: 10.1016/s0925-4439(01)00026-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of mRNAs of antisecretory factor-1, gp96, DAD1 and CDC34 in human hepatocellular carcinomas

Abstract: To identify differentially expressed genes in hepatocarcinogenesis, we performed differential display analysis using surgically resected hepatocellular carcinoma (HCC) and adjacent non-tumorous liver tissues. We identified four cDNA fragments upregulated in HCC samples, encoding antisecretory factor-1 (AF), gp96, DAD1 and CDC34. Northern blot analysis demonstrated that these mRNAs were expressed preferentially in HCCs compared with adjacent non-tumorous liver tissues or normal liver tissues from non-HCC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 57 publications
3
51
0
Order By: Relevance
“…These findings are consistent with a previous study suggesting that CDC34 is upregulated in malignant versus normal plasma cells (De Vos et al, 2002). Moreover, higher levels of CDC34 transcripts have also been reported in acute lymphoblastic leukemia and hepatocellular carcinomas (Tanaka et al, 2001). Together, these findings suggest that CDC34 may regulate the growth of tumor cells.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with a previous study suggesting that CDC34 is upregulated in malignant versus normal plasma cells (De Vos et al, 2002). Moreover, higher levels of CDC34 transcripts have also been reported in acute lymphoblastic leukemia and hepatocellular carcinomas (Tanaka et al, 2001). Together, these findings suggest that CDC34 may regulate the growth of tumor cells.…”
supporting
confidence: 92%
“…A recent report showed a high expression of CDC34 in pediatric T-cell acute lymphoblastic leukemia (Eliseeva et al, 2001) and hepatocellular carcinoma (Tanaka et al, 2001); however, the mechanism regulating CDC34 in cancer cells has not been characterized.…”
mentioning
confidence: 99%
“…Of note, this gene has already been reported to be upregulated in acute lymphoblastic leukemia and hepatocellular carcinomas (Tanaka et al, 2001). CDC34 is a ubiquitin-conjugating enzyme that appears to play a particularly important role in the control of the cell cycle in budding yeast and Xenopus (Michael and Newport, 1998).…”
Section: Myc and Myc Partnersmentioning
confidence: 99%
“…We previously reported the identification of an HBV-specific HLA class I specific peptide bound to gp96 in HCC patients [17,18] , indicating its possible roles in immunity of HBV-induced HCC patients. At the same time, a Japanese group showed that gp96 expression level in HCC patients increased [19] and implied its effect on tumorigenicity. It is estimated that 350-400 million people worldwide are persistently infected with HBV and some of these persistent infected patients develop into cirrhosis or HCC in later stage [20,21] .…”
Section: Introductionmentioning
confidence: 96%